THIN LAYER PHOTOCATALYSTS OF TiO₂-Ag COMPOSITES - TEGZE, Borbála; ALBERT, Emőke; DIKÓ, Boglárka; MADARÁSZ, János; SÁFRÁN, György; HÓRVÖLGYI, Zoltán (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Mesoporous TiO2 coatings were prepared by sol-gel dip-coating method on glass and SiO2 coated glass substrates. They were modified with silver by two different methods: impregnation of as-prepared coatings in AgNO3 aqueous solution; coating deposition from precursor sols containing AgNO3. Transmittance spectra, refractive index, layer thickness and porosity were determined by UV-Vis spectroscopy. Crystallinity of the samples was characterized by XRD, and the morphology and structure by HR-TEM. Photoinduced wettability conversion of the samples was studied, and it was found that the presence of the SiO2 barrier layer and the silver content had significant effect on the wetting behaviour. The photoactivity and reusability of the samples were investigated with methyl orange dye degradation under ultra-violet (UV) irradiation. TiO2 coatings impregnated in 1M AgNO3 solution were found to be the most stable photocatalyst system.